Ultrasonic vocal communication of negative affective states in laboratory mice - Hideaki Inagaki; Takahiro Ushida (Proceedings of the National Academy of Sciences, 2026)
Anxiety disorders are the most common mental disorders, resulting in substantial social and economic costs stemming from reduced productivity. Pharmacotherapy is the most widely used treatment for these disorders, and effective improvement requires a reliable animal model of human anxiety. Although communication in rats using ultrasonic vocalizations (USVs) has been reported as a biologically valid animal model of human anxiety, an equivalent model in mice has not yet been established. To identify such USVs, we conducted physiological, behavioral, and pharmacological experiments using ddY strain mice. Ultrasonic sine waves within a limited frequency range enhanced anxiety levels in male mice. When female mice were exposed to ethologically stressful situations, they emitted a specific type of USV that was not only quantitatively abundant and qualitatively distinct but also within a frequency range that induced increased anxiety in male mice. Playback of these female USVs induced anxiety-related affective changes in male mice. We believe that these findings represent a step toward demonstrating ultrasonic vocal communication of negative affective states in laboratory mice. This study offers a foundation for developing mouse models using USVs as a tool to understand the pathogenic mechanisms of human anxiety disorders and to develop neuropharmacological therapies.